Functional Characterization of the Monogalactosyldiacylglycerol Synthase Gene ptMGD2 in the Diatom Phaeodactylum tricornutum - Shang, Shuo; Liu, Ruyi; Luo, Ling; Li, Xitong; Zhang, Shengqiang; Zhang, Yi; Zheng, Peng; Chen, Zhuo; Wang, Baoshan (Frontiers in Marine Science, 2022)
Monogalactosyldiacylglycerol (MGDG) is the most abundant polar lipid in thylakoid membrane, wherein it plays critical roles related to thylakoid membrane assembly and function in diatoms. However, diatom MGDG biosynthesis has not been fully characterized. In this study, we investigated the role of a novel MGDG synthase (ptMGD2), which is one of the key enzymes for MGDG biosynthesis, in the model diatom Phaeodactylum tricornutum. An analysis of subcellular localization demonstrated that the ptMGD2 is mainly localized in plastids. Gene disruption by gene editing of ptMGD2 resulted in delayed growth, decrease in oxygen evolution rate, reduced MGDG and digalactosyldiacylglycerol (using MGDG as the substrate) content as well as lipid remodeling. Considered together, these observations provide novel insights into the importance of ptMGD2 for regulating MGDG biosynthesis and its potential roles in biotechnical application of Phaeodactylum.